Strategi Keputusan Pembelian melalui Store Atmosphere, Kualitas Pelayanan dan Lokasi dengan Kepuasan Konsumen sebagai Variabel Intervening - Nunuk Herawati; Endang Brotojoyo (ProBank, 2025)
This study investigates the strategy of purchasing decisions through store atmosphere, service quality, and location with customer satisfaction as a mediating variable. Using a quantitative approach and path analysis, the study finds that store atmosphere, service quality, and location positively influence customer satisfaction, while purchasing decisions also show a positive impact. T-test results indicate that service quality, location, and purchasing decisions significantly affect customer satisfaction; however, store atmosphere does not. The coefficient of determination (RÂ²) reveals that store atmosphere, service quality, and location explain 30.7% of purchasing decisions. When customer satisfaction is included as a mediator, the explanatory power increases to 74.2%, indicating its substantial mediating role. Correlation analysis shows strong relationships among all variables studied. Direct effects indicate that store atmosphere and location significantly influence purchasing decisions, while indirect effects show that only service quality effectively uses customer satisfaction as a mediator in influencing purchasing decisions. In conclusion, customer satisfaction plays a crucial intervening role, especially in mediating the effect of service quality on purchasing decisions.